HUBUNGAN KEMAMPUAN NUMERIK DENGAN HASIL BELAJARMATEMATIKA SISWA SMP YLPI PERHENTIAN MARPOYAN PEKANBARU (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This research is a correlational research aimed to determine the relation of numerical ability with mathematics student learning outcomes SMP YLPI Perhentian Marpoyan Pekanbaru. To determine the numerical ability of students used the numerical ability tests. Data were analyzed using descriptive analysis and inferential analysis. From the analysis results obtained strong relation between numerical abilitywith mathematics student learning outcomes SMP YLPI Perhentian Marpoyan Pekanbaru expressed by rxy = 0.606. Then the contribution of numerical ability to mathematics student learning outcomes is 36.72%. Hypothesis testing shows that there is a significant correlation between numerical ability and mathematics student learning outcomes, this is indicated by tcount = 8,83 and ttable = 2,000 for tcount>ttable then the hypothesis is accepted. It can be concluded that there is a significant correlation between numerical ability with mathematics student learning outcomes SMP YLPI Perhentian Marpoyan Pekanbaru.Keywords: Numerical Ability, Mathematics Learning Outcomes, Relation